2006
DOI: 10.1128/mcb.00222-06
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Regulation of Ad4BP/SF-1 Gene Transcription during Fetal Adrenal Development: Initiation by a Hox-Pbx1-Prep1 Complex and Maintenance via Autoregulation by Ad4BP/SF-1

Abstract: The orphan nuclear receptor Ad4BP/SF-1 (adrenal 4 binding protein/steroidogenic factor 1) is essential for the proper development and function of reproductive and steroidogenic tissues. Although the expression of Ad4BP/SF-1 is specific for those tissues, the mechanisms underlying this tissue-specific expression remain unknown. In this study, we used transgenic mouse assays to examine the regulation of the tissue-specific expression of Ad4BP/SF-1. An investigation of the entire Ad4BP/SF-1 gene locus revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
121
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 59 publications
5
121
0
Order By: Relevance
“…14 The greater degree of staining observed in female adrenals is consistent with reports of more prominent female X zone development. 12,36 Emergence of radial stripes in the developing 21OH/LacZ adrenal cortex.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tsupporting
confidence: 78%
See 2 more Smart Citations
“…14 The greater degree of staining observed in female adrenals is consistent with reports of more prominent female X zone development. 12,36 Emergence of radial stripes in the developing 21OH/LacZ adrenal cortex.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tsupporting
confidence: 78%
“…Elegant transgenic lineage analyses of mouse adrenocortical organogenesis and maintenance have shown (1) that distinct groups of fetal adrenocortical cells with a common origin form the X zone and definitive adult adrenal cortex 14,15 and (2) that progenitor cells labeled at E14.5 can produce clones of cells that span the cortex and produce all the steroidogenic cell types of the adrenal cortex. 22 Our present results bridge these two observations and show that perinatal adrenal cortical growth occurs by edge-biased growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that Sf-1 was dispensable for the initiation of expression of its own fetal adrenal enhancer. It was nonetheless required at later stages of development as shown by the absence of expression of the mutated transgene in the E17.5 adrenal [3]. Interestingly, mice lacking Pbx1, a member of the TALE family of homeodomain transcription factors, lacked adrenals at E14.5, had rudimentary gonads (but no sex reversal) and showed renal abnormalities.…”
Section: Fetal Adrenal Enhancer (Fade)mentioning
confidence: 99%
“…This 600 bp enhancer fragment is contained in the fourth intron of Sf-1 and was shown to drive specific reporter gene expression to the adrenal primordium of transgenic mice, as early as E10.5 [3]. Therefore, this DNA region was called Fetal Adrenal Enhancer or FAdE.…”
Section: Fetal Adrenal Enhancer (Fade)mentioning
confidence: 99%